2012
DOI: 10.1186/1471-2458-12-933
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic randomised trial of a 12-week exercise and nutrition program for Aboriginal and Torres Strait Islander women: clinical results immediate post and 3 months follow-up

Abstract: BackgroundAboriginal and Torres Strait Islander women experience higher rates of heart disease and type 2 diabetes than non-Indigenous Australian women. Increasing physical activity, improving diets and losing weight have been shown to reduce cardio metabolic risk. The primary aim was to evaluate the effectiveness of a 12-week structured exercise and nutrition program in a cohort of urban Indigenous Australian women on waist circumference, weight and biomedical markers of metabolic functioning from baseline (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
159
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(165 citation statements)
references
References 13 publications
5
159
1
Order By: Relevance
“…Of the 51 included studies (18 480 participants), 44 were RCTs28–70 and seven were cluster RCTs71–77 conducted in Europe (n=25), the USA (n=18), Australia (n=7) and China (n=1). The majority of studies were carried out in a mixed gender population (n=35); 13 studies targeted women only29 42 50 51 56 57 60 61 67 69 71 76 and three studies targeted men only 29 31 44. Most studies included participants aged between 18–60 years (n=44), while seven studies included participants older than 60 years of age 33 35 37 38 48 62 72.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 51 included studies (18 480 participants), 44 were RCTs28–70 and seven were cluster RCTs71–77 conducted in Europe (n=25), the USA (n=18), Australia (n=7) and China (n=1). The majority of studies were carried out in a mixed gender population (n=35); 13 studies targeted women only29 42 50 51 56 57 60 61 67 69 71 76 and three studies targeted men only 29 31 44. Most studies included participants aged between 18–60 years (n=44), while seven studies included participants older than 60 years of age 33 35 37 38 48 62 72.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies employed an intervention specifically to reduce SB,40 44 63 16 studies aimed at increasing PA levels,30 35 36 39 41 46 48 49 55 58–60 64 66 72 78 nine studies combined both approaches of reducing SB and increasing PA levels,32 43 53 62 65 68 70 76 77 one study assessed the effect of a dietary intervention on SB,61 and 22 studies (20 reports) applied a multicomponent lifestyle intervention and observed effects on sedentary behaviour (among other outcomes) 29 33 34 37 38 42 45 47 50–52 54 56 57 67 69 71 73 74 75. Twenty studies offered an alternative intervention,30 36 39–41 45 46 49 52–55 59 61–63 68 72 77 10 studies the usual/routine care,29 37 38 42 50 51 67 71 74 75 seven studies used a waiting list control,29 34 48 64 69 76 78 five studies an attention control,35 44 56 57 60 and control participants of seven studies received no intervention at all 32 33 43 47 58 66 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Internationally, there have been some interventions for indigenous people, for reducing T2DM prevalence [5,[7][8][9][10][11][12] or that aimed to reduce obesity, CVD and diabetes risk [13][14][15]. These interventions most commonly included exercise [10][11][12][13][14] and/or dietary education [5,9,13,14].…”
Section: Introductionmentioning
confidence: 99%